Adaptive Learning Technologies in Arabic Language Education: Designing for Flexibility and Accessibility - Keumalawati, Cut; Hossam, Ahmed (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Arabic language education faces the challenge of providing flexible and accessible learning methods to a diverse range of students with different levels of ability. Adaptive learning technologies are considered a potential solution to address these challenges by allowing for the customization of learning materials and experiences according to individual needs. Purpose. This study aims to explore the use of adaptive learning technology in Arabic language education, with a focus on flexibility and accessibility for students. Method. This study uses a quasi-experimental design by involving students who use adaptive learning platforms. Data is collected through pre-test and post-test tests as well as student engagement surveys during the learning process. Results. The results showed that students who used adaptive learning technology experienced a significant improvement in test scores and showed higher engagement compared to students who used conventional learning methods. This system provides a more personalized learning experience and is tailored to the individual needs of students. Conclusion. This study concludes that adaptive learning technology can be an effective solution in Arabic language education, by improving learning outcomes and student engagement. However, external support from teachers is still needed to maximize the effectiveness of this system.